Beliefs Attitudes and Communicative Practices of Opponents and Supporters of COVID-19 Containment Policies: A Qualitative Case Study from Germany - Schieferdecker, David (Javnost-The Public, 2021)
In many countries, intense political contestation unfolded around the question of how Sars-CoV-2 should be contained. In this case study, I try to understand why members of the German public came to vastly differing judgements on the containment policies. In summer 2020, I conducted 48 semi-structured interviews to investigate respondents’ belief systems, attitude structures, and communicative practices. I found that disparate policy preferences were partly based on incompatible interpretations of the crisis and went hand in hand with deep institutional mistrust between strict opponents. Stereotypes about supporters and opponents had formed, and people avoided discussions with opposing camps. However, my data also suggest that moderate opponents and supporters overlapped in their criticism of anxiety-inducing media coverage and fuzzy governmental communication. No fully-fledged social identities had formed, and respondents were forcibly exposed to other opinions in their close personal networks. Altogether, my study extends the knowledge of political polarisation around COVID-19 by unravelling the interpretations and mechanisms that underlie disparate policy preferences during the pandemic.